2022
DOI: 10.1186/s13071-022-05460-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of native cyclopoid copepods in biological vector control with regard to their predatory behavior against the Asian tiger mosquito, Aedes albopictus

Abstract: Background The control of the Asian tiger mosquito Aedes albopictus (Diptera: Culicidae) is crucial owing to its high vector competence for more than 20 arboviruses—the most important being dengue, chikungunya and Zika virus. Aedes albopictus has an enormous adaptive potential, and its invasive spreading across urban and suburban environments poses challenges for its control. Therefore, all suitable, cost-effective and eco-friendly control tools should be put into practice. In this context, cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Aedes larvae have previously displayed higher motility than Culex larvae (Dieng et al, 2003, Kesavaraju et al, 2011), and higher larval activity has been associated with greater vulnerability to predation (Grill and Juliano, 1996). These findings are consistent with studies that have shown a preference for Aedes prey, rather than Culex , among cyclopoid copepod predators (Dieng et al, 2003, Soumare and Cilek, 2011, Pauly et al, 2022). However, the body size of prey organisms is also an important determinant of vulnerability to predation; cyclopoid copepods have been shown to prefer smaller species of rotifer prey and have caused greater mortality among fish larvae of smaller body lengths (Kumar et al, 2012, Lapesa et al, 2002).…”
Section: Introductionsupporting
confidence: 92%
“…Aedes larvae have previously displayed higher motility than Culex larvae (Dieng et al, 2003, Kesavaraju et al, 2011), and higher larval activity has been associated with greater vulnerability to predation (Grill and Juliano, 1996). These findings are consistent with studies that have shown a preference for Aedes prey, rather than Culex , among cyclopoid copepod predators (Dieng et al, 2003, Soumare and Cilek, 2011, Pauly et al, 2022). However, the body size of prey organisms is also an important determinant of vulnerability to predation; cyclopoid copepods have been shown to prefer smaller species of rotifer prey and have caused greater mortality among fish larvae of smaller body lengths (Kumar et al, 2012, Lapesa et al, 2002).…”
Section: Introductionsupporting
confidence: 92%
“…The disadvantage of the majority of larvicides providing only a limited effect can potentially be compensated by the simultaneous inoculation of natural predators to the breeding sites, to feed upon newly hatched larvae as the impact of larvicides ceases. These predators should therefore maintain stable populations within bodies of water, creating a sustainable, long-term vector control [ 1 , 111 , 112 ]. In this context, copepods are considered to be the most efficient invertebrate predators of mosquito larvae and are a promising tool in the control of container-breeding mosquitoes [ 111 ].…”
Section: Pillar I—community Participationmentioning
confidence: 99%
“…These predators should therefore maintain stable populations within bodies of water, creating a sustainable, long-term vector control [ 1 , 111 , 112 ]. In this context, copepods are considered to be the most efficient invertebrate predators of mosquito larvae and are a promising tool in the control of container-breeding mosquitoes [ 111 ]. The use of copepods against Aedes mosquitoes was primarily described 1981 by Riviere and Thirel [ 113 ].…”
Section: Pillar I—community Participationmentioning
confidence: 99%
See 2 more Smart Citations